Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1021/acsnano.3c00649
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically-Achievable Injectable and Sprayable in Situ Lyotropic Liquid Crystalline Platform in Treating Hormone-Sensitive and Castration-Resistant Prostate Cancer

Abstract: When it comes to long-acting injections, lyotropic liquid crystals (LLCs) are considered as an effective and powerful drug delivery technology due to their low manufacturing and injection difficulty, consistent releasing behaviors with low burst, as well as broadly applicable drug loading capacity. However, monoolein and phytantriol, as two widely used LLC-forming materials, may give rise to tissue cytotoxicity and undesired immunological responses, which may hinder the wide application of this technology. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Lyotropic liquid crystalline technology could accommodate drugs with different properties, and release incorporated drugs in a controlled and prolonged manner . To evaluate the releasing behaviors of donepezil hydrochloride and cilostazol-loaded LLC gel implants, both in vitro and in vivo releasing tests were performed (Figure A–D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lyotropic liquid crystalline technology could accommodate drugs with different properties, and release incorporated drugs in a controlled and prolonged manner . To evaluate the releasing behaviors of donepezil hydrochloride and cilostazol-loaded LLC gel implants, both in vitro and in vivo releasing tests were performed (Figure A–D).…”
Section: Resultsmentioning
confidence: 99%
“…27,28 Besides, the situ-forming technology of LLC implants enables direct injection with low injecting difficulty, and avoids surgical embedding, which is different from traditional gel implants. 29,30 In this study, we incorporated donepezil hydrochloride and cilostazol into phosphatidylcholine and α-tocopherol-based lyotropic liquid crystalline implants, and found that when compared with daily oral delivery of donepezil hydrochloride +cilostazol solution (DCS) and subcutaneous delivery of donepezil hydrochloride+cilostazol-loaded LLC gel implant (DCG), administrating DCG near the dCLNs achieved the greatest drug concentrations in brains. Encouraged by this, we constructed old AD mice by injected Aβ 1−42 into bilateral hippocampus of the mice aged 20 months, and compared the therapeutic efficacy between different administration strategies on the elderly AD mice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrophobic groups in the molecule are usually arranged side-by-side [ 61 ]. Due to its spontaneous phase transition characteristics, ordered lattice structure, excellent drug loading, good biosafety and biocompatibility [ 62 , 63 ], release profile and stabilization of various drugs [ 64 ], it is expected to act as a prospect candidate delivery system for chronic wound treatment. LLC not only has a healing effect on the wound, but also can be useful as a nano drug carrier in implants [ 65 , 66 ].…”
Section: Lyotropic Liquid Crystalline Might Be a Promising Candidate ...mentioning
confidence: 99%